2016
DOI: 10.2116/analsci.32.1291
|View full text |Cite
|
Sign up to set email alerts
|

A Near Infrared Fluorescent Probe for Sensitive Determination of Human Serum Albumin

Abstract: A fluorescent probe 1 has been successfully developed to determine human serum albumin (HSA). Probe 1 expresses a dramatic fluorescence enhancement to HSA without interference from other amino acids. Under the optimal conditions, the calibration graphs are linear over the range of 0 -13.3 μg/mL with the limit of determination of 0.61 μg/mL. Thus, this probe shows high sensitivity and selectivity to HSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Then, the selectivity of S1 toward HSA was assessed by testing cargo release against common interfering molecules present in biological samples. Figure 4 shows the emission of rhodamine B (at 571 nm) released from S1 nanoparticles suspended in PBS (pH 7.4)-acetonitrile 95:5 v / v in the presence of HSA and other selected interfering molecules such as anions, cations, amino acids, urea (at 10 μM) and synthetic urine in PBS [ 43 ]. As could be seen, only HSA was able to induce pore opening and rhodamine B release.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the selectivity of S1 toward HSA was assessed by testing cargo release against common interfering molecules present in biological samples. Figure 4 shows the emission of rhodamine B (at 571 nm) released from S1 nanoparticles suspended in PBS (pH 7.4)-acetonitrile 95:5 v / v in the presence of HSA and other selected interfering molecules such as anions, cations, amino acids, urea (at 10 μM) and synthetic urine in PBS [ 43 ]. As could be seen, only HSA was able to induce pore opening and rhodamine B release.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Recently, external fluorescent probe based detection technique has attracted much attention of the bioanalytical chemists. [18][19][20][21][22] Fluorescent based tools are costeffective, non-invasive, and rapid in nature. However, a suitable fluorophore is always required for the detection and quantification of HSA in complex biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…For example, research has shown that there is an intimate connection between cardiovascular disease and kidney damage, and the critical indictor for kidney damage is the concentration of HSA in human urine [ 5 ]. Several methods to determine the concentration of HSA have been developed, including visible absorption spectroscopy [ 6 , 7 , 8 ], electrochemical [ 9 , 10 ], Immunoassays [ 11 , 12 , 13 ] and High-performance liquid chromatography (HPLC) [ 14 ]; however, there are some problems for detecting the concentration of HSA with these methods. For example, Tu and co-workers reported a low-cost method with Immunoassays to detect the HSA [ 15 ].…”
Section: Introductionmentioning
confidence: 99%